2022
DOI: 10.3389/fpubh.2022.891546
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Foods Elicit Higher Approach Motivation Than Unprocessed and Minimally Processed Foods

Abstract: BackgroundUltra-processed foods (UPF) are becoming extensively available in the food environments. UPF are industrial formulations that are designed to maximize palatability and consumption through a combination of calorie-dense ingredients and chemical additives. UPFs are also aggressively marketed, which may make them more attractive than unprocessed/minimally processed foods (UMPF). Since consumers' purchase decisions are guided by food-evoked emotions, we aimed to provide evidence that UPF visual cues trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
0
7
1
Order By: Relevance
“…Hyperpalatability has also been suggested to be important for food choice and consumption (35) . Many ultra-processed foods have hyper-palatable properties, such as combinations of fat and sugar not usually seen in nature, which have been proposed to have addictive-like qualities by inducing a greater hedonic response when consumed, increasing reward-driven eating (20,35,39) . In the metabolic ward study, both energy density (45•1 ± 13•6 %) and hyper-palatability (41•9 ± 6•5 %) explained large proportions of the greater daily non-beverage energy intake on the ultra-processed v. minimally processed diet (40) .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperpalatability has also been suggested to be important for food choice and consumption (35) . Many ultra-processed foods have hyper-palatable properties, such as combinations of fat and sugar not usually seen in nature, which have been proposed to have addictive-like qualities by inducing a greater hedonic response when consumed, increasing reward-driven eating (20,35,39) . In the metabolic ward study, both energy density (45•1 ± 13•6 %) and hyper-palatability (41•9 ± 6•5 %) explained large proportions of the greater daily non-beverage energy intake on the ultra-processed v. minimally processed diet (40) .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings add to the theoretical and empirical evidence suggesting that perceived resilience, perceived stress, and diet quality increase with age and are therefore modifiable. Considering that addressing mental health in behavioral intervention research is becoming increasingly important, resilience may be an important starting point in the development of effective dietary interventions for CVD prevention at all ages, but especially among early young adults (18)(19)(20)(21)(22)(23)(24) [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Also, multilevel barriers have made it stressful for Americans to engage in healthy eating [ 17 , 18 , 19 ]. Over the past few decades, the food system has been flooded with aggressively marketed ultra-processed foods and sugar-sweetened drinks, making it psychologically taxing to engage in healthy eating [ 20 , 21 , 22 , 23 , 24 ]. Thus, identifying psychological assets that can serve as a stress buffer could be a key protective strategy to improving and sustaining a better diet quality, particularly in vulnerable populations [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests UPFs may be ‘wanted’ more, but do not seem to be ‘liked’ to a greater extent during consumption. Before consumption, images of UPFs generate a strong appetitive drive [ 80 ], with greater motivational reactivity than MPFs or PFs [ 81 ], and greater approach motivation and intent to consume than MPFs [ 82 ]. During and after consumption, early preliminary evidence suggested that MPFs had a higher satiety potential than UPFs [ 83 , 84 ].…”
Section: Mechanisms: What Drives the Effect?mentioning
confidence: 99%